Cultivating Noble Character through Experiential Learning: Reflections on Buddhist Character Education in Vesak Celebration in Medan-Indonesia - Kumari, Winja (Yayasan Ilomata, 2024)
This study examines the influence of Vesak celebrations in developing noble character through experiential learning, involving 100 participants in Medan as a sample. Using a quantitative approach and Structural Equation Modeling with Partial Least Squares (SEM-PLS) analysis, the study examined how participation in meditation, chanting, alms offering, and charitable activities during Vesak contributed to the development of traits such as compassion, wisdom, mindfulness, and ethical behavior. The results showed a significant positive relationship between all Vesak activities and the improvement of noble qualities, with meditation and almsgiving having the greatest impact. The fit index showed a solid model fit, confirming the validity of the model. The findings emphasize the effectiveness of religious celebrations as a means of character education and provide insights for integrating experiential learning in moral development programs.